Scalable synthesis of dispersible iron carbide (Fe3C) nanoparticles by 'nanocasting'. Issue 33 (9th August 2019) - Fletcher, D. C.; Hunter, R.; Xia, W.; Smales, G. J.; Pauw, B. R.; Blackburn, E.; Kulak, A.; Xin, Huolin; Schnepp, Z.
Abstract : MgO powder is used as a removable 'cast' in a simple, scalable synthesis of dispersible Fe3 C nanoparticles. Abstract : Metal carbides have shown great promise in a wide range of applications due to their unique catalytic, electrocatalytic and magnetic properties. However, the scalable production of dispersible metal carbide nanoparticles remains a challenge. Here, we report a simple and scalable route to dispersible iron carbide (Fe3 C) nanoparticles. This uses MgO nanoparticles as a removable 'cast' to synthesize Fe3 C nanoparticles from Prussian blue (KFe III [Fe II (CN)6 ]). Electron tomography demonstrates how nanoparticles of the MgO cast encase the Fe3 C nanoparticles to prevent sintering and agglomeration during the high-temperature synthesis. The MgO cast is readily removed with ethylenediaminetetraacetic acid (EDTA) to generate Fe3 C nanoparticles that can be used to produce a colloidal ferrofluid or dispersed on a support material.